HATE SPEECH: CONCEPT AND PROBLEM - Rumadi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
Hate speech issues have become one of interesting topics disscussed by academics of different disciplines since two decades ago. The studies employ various perspectives such as linguistics, sociology, anthropology, psychology, politics, law and even media and communication, making the theme an interdisciplinary study. One of prominent and comprehensive studies on hate speech in US from 1920s to the end of twenty century using social and political history perspective is one written by Samuel Walker (1994), a professor in University of Nebraska, Omaha, AS. Walker focused the study on social context and groups interrelation, prejudice and discrimination as political issues, and attempts to control hate speech through legal institutions. Started from terminology analysis like “race hate”, “group libel”, or “racist speech”, Walker then proposed a definition of hate speech and its related expressions such as race, ethnic, religious groups, minority, age, marital status, physical capacity, sexual preference and sex